Biologically inspired deep residual networks - Prathibha Varghese; Arockia Selva Saroja (Institute of Advanced Engineering and Science, 2023)
Many difficult computer vision issues have been effectively tackled by deep neural networks. Not only that but it was discovered that traditional residual neural networks (ResNet) captures features with high generalizability, rendering it a cutting-edge convolutional neural network (CNN). The images classified by the authors of this research introduce a deep residual neural network that is biologically inspired introduces hexagonal convolutions along the skip connection. With the competitive training techniques, the effectiveness of several ResNet variations using square and hexagonal convolution is assessed. Using the hex-convolution on skip connection, we designed a family of ResNet architecture,hexagonal residual neural network (HexResNet), which achieves the highest testing accuracy of 94.02%, and 55.71% on Canadian Institute For Advanced Research (CIFAR)-10 and TinyImageNet, respectively. We demonstrate that the suggested method improves vanilla ResNet architectures’ baseline image classification accuracy on the CIFAR-10 dataset, and a similar effect was seen on the TinyImageNet dataset. For Tiny- ImageNet and CIFAR-10, we saw an average increase in accuracy of 1.46% and 0.48% in the baseline Top-1 accuracy, respectively. The generalized performance of advancements was reported for the suggested bioinspired deep residual networks. This represents an area that might be explored more extensively in the future to enhance all the discriminative power of image classification systems.